Global competence for the future : employability, mobility, quality collaboration and current developments - Schreiber, Elmar; Berninghausen, Jutta (Intercultural studies, 2008)
More and more countries in Europe started a challenging change following the vision of a common "European Higher Education Area" which has taken on structure and shape within the scope of the Bologna process. The internationalization of universities is a response to the challenges of globalization, and is one of the most important objectives of the Bologna Process. The key aims of the Bologna Process are directed toward the comparability of educational systems, more transparency, and verifiable educational contents, in order to establish the same standards in higher education across Europe.